Toxicological Trends Of Poisoning At Tertiary Care Hospital In Ahmedabad: A Retrospective Study (Indian Journal of Forensic Medicine & Toxicology, 2024)
Poisoning is a major problem all over the world, though the type of poison and the associatedmorbidity and mortality varies from place to place and changes over a period of time.A retrospective study of 154 cases of poisoning received in the casualty of G.C.S. Medical College, Hospital and Research Centre, Ahmedabad during a span of last 3 years (Jan 2021 to Dec 2023) was done to know the demographic profile and pattern of acute poisoning in the region.Knowing the pattern of poisoning cases in a region helps in suggesting proper earliest preventive measures and also in early management of cases. Out of total cases majority of the cases were male (36 %), unmarried (54.5 %), and most commonly affected age group was 31 to 40 years (19.5 %). Household poisoning cases (21.43 %) were the most common type of poisoning. Majority of the cases intentionally consumed poison(56.50 %). Oral ingestion was the most common route of exposure (94.8 %).
Keywords: Poisoning; Toxins; Suicide